Treatment of non-melanoma superficial skin cancer with custom-made wax moulds using Iridium-192 high-dose-rate brachytherapy source. Issue 1 (24th August 2017) - Shah, Kamran Ali; Ahmad, Habib; Khatak, Muhammad Rauf; Ahmad, Misbah; Javed, Nabila; Shah, Syed Jawad Ali; Shaheen, Wajeeha
Abstract: Introduction: In non-melanoma skin cancer—that is, basal cell carcinoma (BCC) and squamous cell carcinoma (SCC)—brachytherapy treatment is preferred over surgical excision because of cosmetic reasons, acceptability and preference of patients. Material and methods: Moulds are prepared of wax to match the size of the lesion. This represents the area to be considered in treatment planning. A total of 85 patients who had either SCC or BCC were treated, and all these patients were classified on the basis of age, gender and origin. Results: Patients were treated with 39 Gy in 13 fractions (biological effective dose=50·7 Gy). In 52 BCC patients, treatment achieved excellent cosmetic results in 49 cases, with 17 of these patients experiencing Grade-1 skin reactions related to treatment in the first 24 weeks of follow-up. A single patient experienced Grade-II hyper-pigmentation reaction in the third week. In 33 SCC patients, treatment achieved excellent cosmetic results in 28 cases, with 17 of these patients experiencing Grade-I reaction in the first 36 weeks after treatment. Among the remaining four patients, only one developed Grade-II hypo-pigmentation and one patient experienced tumour recurrence near the primary site. The overall outcome efficacy of the treatment was 98·8%. Findings: The treatment outcome not only enhances our confidence in brachytherapy but also improves the patient's satisfaction regarding cosmetic results and curative output achieved by avoiding a surgical procedure for non-melanoma skin cancers.